7α-acetoxy-6β-hydroxyroyleanone (Roy) modulates IL-6/STAT3/JAK2 mRNA expression and suppresses tumor growth in glioblastoma cell models - Magalhães, Mariana; Spigarelli, Renato; Domínguez-Martín, Eva María; Ferreira, Lino; Efferth, Thomas; Rijo, Patrícia; Spisni, Enzo; Cabral, Célia (Frontiers in Pharmacology, 2026)
IntroductionGlioblastoma (GB) is the most aggressive primary glioma, with a median survival of 15-18 months. Current treatments are often ineffective, largely due to tumor heterogeneity and recurrence. Advances in understanding GB’s molecular landscape and microenvironment have highlighted new therapeutic strategies to fight this life-threatening tumor. Given the pivotal role of natural compounds in drug discovery, those with anti-inflammatory and cytotoxic/cytostatic properties are emerging as promising candidates for GB therapy.MethodsThis study investigates the antitumor and immunomodulatory effects of 7α-acetoxy-6β-hydroxyroyleanone (Roy), a diterpene isolated by our team from Plectranthus hadiensis Schweinf., using both 2D and 3D GB cell models. U87 cells were used as a standard GB model and to generate monocellular and multicellular spheroids (U87, HMC3, and/or HBMEC cells). Both models were treated with 16 µM of Roy, a concentration previously shown to be tumor-specific.ResultsRoy significantly reduced spheroid size and metabolic activity over time, with the most pronounced effects observed in multicellular spheroids. This compound also inhibited cell proliferation by preventing colony formation and downregulating CDK4 and VEGFA mRNA levels. Roy’s bioactivity was enhanced in the presence of conditioned medium (secretome from GB and/or microglia cells), exerting a neuromodulatory effect by modulating IL6/JAK2/STAT3 mRNA expression and by suppressing the secretion of cytokines involved in the chronic inflammatory state within the GB microenvironment. Importantly, Roy was also able to cross the blood-brain barrier.ConclusionThese findings, in line with our previous work, underscore the cytotoxic potential of this natural compound, suggesting Roy as a promising lead candidate for future GB treatment strategies.